Isu-isu pengintegrasian pangkalan data ukur kadaster dan sistem pendaftaran tanah berkomputer - Mariappan, Gengatharan (2006)
The Department of Survey and Mapping Malaysia has introduced the Cadastre Data Management System (CDMS) in the year 1997. One of the main purpose of the CDMS is to repopulate the Digital Cadastral Database (DCDB) for the Departments of Survey and Mapping at all states. On the other hand, The Ministry of Natural Resources and Environmental formaly known as The Ministry of Land and Cooperative Development has also introduced Computerized Land Registration System (CLRS) at the State Land and Mines Offices as well as the Land Offices throughout the country from the year 1995 onwards. The purpose of this system is to ease the registrations of the land titles and land dealings using the computerized system. Both systems are computer based stand-alone system whereby important land informations to be used effectively and effeciently. Therefore, the aim of this research is to investigate issues related to DCDB and CLRS in order to develope a conceptual model that can integrate DCDB and CLRS. The results of this research show that these two systems can be integrated base on procedure and regulation that fit to the technology and digital environment working concept.